Planning, sustainable urbanisation, and the commonwealth : the commonwealth association of planners, past, present and future - Hague, Cliff; Harridge, Clive; Julyan, Bryce; Nik, Ruiz; Tant, Ian (New York, NY : Routledge, 2023)
"By 2050, an additional 2.5 billion people will be living in the world's towns and cities, almost 50 percent of them in the 56 Commonwealth countries. To a significant extent, the future of the planet hangs on how cities and human settlements are managed. It is in our cities that the emissions creating climate catastrophe are stoked, and where change can - and must - make a difference at scale. Food security, water, basic services, migration, shelter, jobs, environment: sustainable urbanisation is about changing direction to strive for a fairer and less environmentally damaging future. This well-illustrated book by authors from around the globe tells how the Commonwealth Association of Planners across five decades has campaigned to make a difference. It also looks ahead, scoping the urgent, practical action that is now required"--
Keywords: City planning; Sustainable development -- Planning; Community development, Urban; City planning -- Forecasting; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development